“It wasn’t about of the knee”. A systematic review of psychological factors in continuity and later-life reintegration to competitive sports (Jóvenes en la Ciencia, 2026)
Population aging and low participation in sports among mature and older adults make competitive sports a key arena for promoting healthy aging. However, re-engagement in sport after periods of inactivity has been little researched from a psychological perspective, despite evidence of the physical, emotional, and social benefits of master's and adapted sports. In this context, it is necessary to identify the psychological factors that facilitate or hinder continuity and return to sport in people aged 40 and over. The aim of this study was to identify and synthesize the available scientific evidence on the psychological and psychosocial factors involved in the practice and reintegration into competitive sports of mature and older adults, emphasizing motivational, emotional, social, and identity-related variables. A systematic review was conducted following PRISMA 2020. Articles were searched for in PubMed, SciELO, Redalyc, and Google Scholar/Academic (2015–2025), in Spanish and English, with open access, focusing on adults ≥40 years of age in competitive or structured sports, which analyzed psychological or psychosocial factors associated with sports practice, continuity, or return to sports. Studies of recreational physical activity without a formal sports component and grey literature were excluded. Of 120 initial records, 11 met the inclusion criteria. Methodological quality was assessed using an ad hoc questionnaire with seven criteria, adapted from Marshall et al. (2023), with predominantly high quality observed. The most consistent motive was the pursuit of health, well-being, and quality of life, articulated in many studies based on Self-Determination Theory. Additionally, a range of psychosocial factors associated with sport participation emerged, whose relevance varied according to athletes’ sporting trajectories and subjective experiences. Among the barriers identified for engaging in sports, health issues and injuries, time constraints, lack of enjoyment, ageist stereotypes, and the limited visibility of older athletes stood out. Psychological factors play a decisive role in initiating, sustaining, and resuming competitive sports in mature and older adulthood. Programs are needed that strengthen self-determined motivation, enjoyment, and social support, that highlight role models who challenge stereotypes of aging, and that reduce structural and symbolic barriers. Future research should incorporate longitudinal designs and specific interventions for reintegration after prolonged inactivity.